Progression from Concentric Left Ventricular Hypertrophy and Normal Ejection Fraction to Left Ventricular Dysfunction - Milani, Richard V.; Drazner, Mark H.; Lavie, Carl J.; Morin, Daniel P.; Ventura, Hector O. (The American journal of cardiology, 2011)
Concentric left ventricular (LV) hypertrophy develops in response to a chronically increased LV afterload and is associated with increased cardiovascular events. Although the progression to systolic and diastolic heart failure is a known consequence of LV hypertrophy, few data are available on the frequency of deterioration to systolic dysfunction in patients with LV hypertrophy who originally had a normal LV ejection fraction. We evaluated the baseline and follow-up characteristics in 1,024 patients with concentric LV hypertrophy and a normal ejection fraction who had paired echocardiograms that were separated by ≥1 year. Systolic dysfunction occurred in 134 patients (13%) after a mean follow-up of 33 ± 24 months. The most common associated variable was interval myocardial infarction, which occurred in 43% of patients. Other risk factors for developing LV systolic dysfunction included QRS prolongation (>120 ms) and elevated follow-up arterial impedance defined as a value >4.0 mm Hg/ml/m 2. Patients with either a prolonged QRS interval or an elevated follow-up arterial impedance had twice the likelihood of developing LV systolic dysfunction, and, if both factors were present, there was a greater than fourfold increased risk of developing systolic dysfunction. Blood pressure measurements alone did not adequately reflect an elevated arterial impedance. In conclusion, 13% of patients with a normal ejection fraction and concentric LV hypertrophy progress to systolic dysfunction during approximately 3 years of follow-up. The risk factors for loss of function were interval myocardial infarction, prolonged QRS, and chronically elevated arterial impedance.